2021
DOI: 10.3390/ijerph18126461
|View full text |Cite
|
Sign up to set email alerts
|

Psychosocial and Diet-Related Lifestyle Clusters in Overweight and Obesity

Abstract: This study explored intraindividual multidimensional profiles integrating psychosocial factors, namely, body image and satisfaction, weight-related self-stigma, positivity, and happiness, and behavioural-lifestyle factors, namely, adherence to a healthy diet, among Spanish adults with overweight or obesity. We further aimed to investigate the association of excess weight (i.e., measured body mass index, BMI) with the abovementioned multidimensional configurations. A convenience sample of 100 adult individuals … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
0
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 80 publications
1
0
0
1
Order By: Relevance
“…Weight and shape concern at all levels had a large moderating effect on the relation between WBI and depressive symptoms. This result goes in line with findings from a cluster analysis revealing that individuals with overweight or obesity and weight concern showed low levels of happiness and positivity [ 56 ]. Similarly, a cross-sectional study demonstrated that WBI was highly correlated with depressive symptoms and weight and shape concern among BSC [ 57 ].…”
Section: Discussionsupporting
confidence: 89%
“…Weight and shape concern at all levels had a large moderating effect on the relation between WBI and depressive symptoms. This result goes in line with findings from a cluster analysis revealing that individuals with overweight or obesity and weight concern showed low levels of happiness and positivity [ 56 ]. Similarly, a cross-sectional study demonstrated that WBI was highly correlated with depressive symptoms and weight and shape concern among BSC [ 57 ].…”
Section: Discussionsupporting
confidence: 89%
“…En referencia a la temática propuesta, existen diversos hallazgos sobre el estilo de vida y la obesidad. Tal es el caso, del estudio realizado por Godoy et al (2021), en el que se enfoca en el objetivo de determinar la influencia de los factores de estilos de vida en el índice de masa corporal, la relación en cuanto al estilo de vida poco saludable y a su exceso de peso.…”
Section: Introductionunclassified